2017
DOI: 10.13189/ujer.2017.050412
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of Some Nationals (North American, South Korean, Chinese, Indian, Turkish, and Latin American) on Some Concepts of Citizenship Education

Abstract: Over years, the meaning of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This result is similar to the findings obtained in this study. In another study carried out by Faiz and Dönmez (2017), volunteering was defined by the participants in the sense of civic engagement, becoming socially beneficial, and feeling of belonging to society. The answers in this study also show that the participants regard volunteering as an action taken on the basis of the benefit of society and helpfulness, without any expectation, willingly and in solidarity / unity and solidarity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is similar to the findings obtained in this study. In another study carried out by Faiz and Dönmez (2017), volunteering was defined by the participants in the sense of civic engagement, becoming socially beneficial, and feeling of belonging to society. The answers in this study also show that the participants regard volunteering as an action taken on the basis of the benefit of society and helpfulness, without any expectation, willingly and in solidarity / unity and solidarity.…”
Section: Discussionmentioning
confidence: 99%
“…Yönten-Balaban and Çoban-İnce (2015) reached that it enabled to gain communication skill, increased the feelings of love and responsibility, instilled selfconfidence and love. In the study by Faiz and Dönmez (2017), it was concluded that volunteering would contribute to personal development, enable individuals to feel belonging to the community in which they led their lives, and enable them to gain sense of responsibility. Coşkun (2012) stated that voluntary activities brought the values of patience, love, respect, helpfulness, responsibility, integrity, sensitivity, mercy, safety and tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation